Customer’s Expectations of Hospitality Services- A Study on Five Star Hotels in Hyderabad City - Bhavani, Ganga (Journal of Management and Science, 2013)
This paper analyzes the customer‘s expectations and their satisfaction levels with regard to services offered by five star hotels in Hyderabad city. A structured questionnaire has been used to obtain feedback from the 150 customers of from five star hotels based on convenience sample method. Statistical tools such as Chi-square and Pearson‘s correlation were employed to validate the results. Findings of the study are (i) there is a relationship between expectations of the customers and the services provided by the star hotels (ii) there is a relationship between customers satisfaction with regard to price charged by the star hotels for the quality of services offered. It is also proved that there is a positive correlation among the above presented parameters. It is suggested that the application of customer relationship management (CRM) is the need of the hour to fulfill the expectations of customerservices.